An Analysis of the Effect of FinTech on Commercial Banks’ Innovation Ability in China - Dong, Aidi (2018)
The emerging FinTech is reshaping the financial industry, accelerating innovation process in banking sector. While FinTech grab customers and resources from traditional commercial banks, it has positive effect on commercial banks. Based on the panel data set of 59 commercial banks from China during 2010 to 2017, this paper empirically investigates the impact of FinTech on commercial banks’ innovation ability, which is measured by income diversification. The result indicates that FinTech lending business has positive effect on banks’ innovation while FinTech payment business shows a negative relationship with bank innovation ability. Further research finds that P2P lending business boosts non-interest income in state-owned commercial banks and regional commercial banks, but it limits the income diversification in joint-stock commercial banks. Conversely, rapid development of FinTech payment business is followed with less income diversification in state-owned commercial banks and regional commercial banks, while joint-stock commercial banks earn more non-interest income with the boom of third-party payment.